PERTIMBANGAN HAKIM DALAM MEMUTUSKAN WALI HAKIM BAGI WANITA YANG TIDAK DIRESTUI WALI NASABNYA DI PENGADILAN AGAMA WATAMPONE KELAS I A - Agustan A. (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2022)
This thesis discusses the consideration of judges in deciding guardian judges for women who are not approved by their lineage guardian (a case study of guardian adhal in the Watampone Religious Court Class 1A). The main problem is what is the procedure for submitting a guardian judge at the Watampone Religious Court Class 1A for women who are not approved by their lineage guardian and how the consideration of the judge at the Watampone Religious Court Class 1A decides for a woman guardian who is not approved by her lineage guardian. This research is a qualitative research that uses methods with two approaches, namely; normative approach, sociological approach. The data in this study were obtained through direct observation and interviews with judges and the public as applicants, namely: Judges at the Watampone Religious Court Class 1A and the community as applicants in Bone Regency. This study aims to determine the procedure for submitting guardian judges for women who are not approved by their lineage guardians and the judge's considerations in deciding guardian judges for women who are not approved by their lineage guardians at the Watampone Religious Court Class 1A. The usefulness of this research is expected to be able to contribute and contribute to the development of legal science, and religion in particular. The results showed that; The procedure for submitting a guardian judge at the Watampone Class 1A Religious Court for women who are not approved by their lineage guardians that; when the bride comes to register her marriage and her lineage guardian is reluctant to marry and does not succeed in making peace, a marriage refusal letter is issued from the Office of Religious Affairs for administrative completeness of the submission of the guardian judge at the Religious Court. The considerations of the judges of the Watampone Class 1A Religious Court in deciding the guardian judge for women who are not approved by their lineage guardians are that; if a woman has agreed to marry a man of the same level (sekufu), the terms and conditions, and there are no barriers for the bride and groom to marry or are not mahram, ask her guardian for marriage and her guardian refuses or does not approve without reason, or reasons that are not in accordance with Islamic law (syara') then the guardian of the lineage is determined to be adhal.